On some properties of 2-D Weyl equation for charged massless spin ½ particle - Ovcharenko, I.E.; Stepanovsky, Yu.P. (Вопросы атомной науки и техники, 2007)
We discuss some properties of Dirac equation and 2-D Weyl equation for a charged massless spin ½ particle in a stationary inhomogeneous magnetic field such as Bloch theorem and Aharonov-Casher theorem and its relation to supersymmetric quantum mechanics. Обговорюються деякі властивості рівняння Дірака та двовимірного рівняння Вейля для зарядженої частинки із спіном ½ у стаціонарному неоднорідному магнітному полі, такі, як теорема Блоха та теорема Ааронова-Кашера, та їх зв’язок з суперсиметричною квантовою механікою. Обсуждаются некоторые свойства уравнения Дирака и двухмерного уравнения Вейля для заряженной частицы со спином ½ в стационарном неоднородном магнитном поле, такие, как теорема Блоха и теорема Ааронова-Кашера, и их связь с суперсимметричной квантовой механикой.